Factors Affecting The Interest Of Women Of Reproductive Age Regarding Visual Inspection Of Acetic Acid (IVA) - Pardosi, Maida; Silitonga, Melva (Postgraduate, University of Mataram, 2024)
Reproductive health is a multidimensional state of physical, mental, and social well-being, covering all aspects of the reproductive system, functions, and processes. Cervical cancer is abnormal cell growth and development, which can lead to abnormal function of the reproductive organs and generally affects women of reproductive age, so the impact on the family is very significant. This study aims to determine the factors between the level of knowledge, access to information, and husband/family support with low Acetic Acid Visual Inspection (IVA) visits. This type of research is survey research with an analytical approach cross-sectional. The samples taken were 67 respondents obtained by the technique of purposive Sampling. The instrument used is a questionnaire. The data obtained is processed using a test Chi Square with a degree of significance (α) = 0.05. The results showed that there was a significant influence between the factors associated with the low number of IVA visits, namely the level of knowledge, access to information, and husband/family support. In the statistical test, the p-value is 0.000. The conclusions of WUS researchers who are married should always pay attention to their reproductive health, one of which is the IVA examination.